2018
DOI: 10.1186/s40981-018-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of ventilatory impairment during per-oral endoscopic myotomy under general anesthesia

Abstract: We report a case of unexpected ventilatory impairment that occurred during per-oral endoscopic myotomy (POEM) under general anesthesia. A 73-year-old woman underwent POEM for Jackhammer esophagus. The patient developed hypercarbia, pneumoperitoneum, and severe subcutaneous emphysema during the operation. Although she was treated with abdominal paracentesis, it became difficult to ventilate her lungs a few minutes later. We recommended the surgeons to interrupt the procedure and proposed repeating the abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…However, the abdominal decompression rates of this study are similar to those reported by Löser and Familia and colleagues, but were higher than those reported by Nishihara 14%, Darisetty 12.3%, and Shivakunun 11% 9,20,21,23,24. The abdominal decompression rates in this study are higher than those reported in other studies because of a longer duration for mucosal tunnel and myotomy in the current study, resulting in longer insufflation duration 25. When blood gas samples were examined in this stage, acidosis was identified in ABG indicating that submucosal and mediastinal absorption of CO 2 was greater than excretion with ventilation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the abdominal decompression rates of this study are similar to those reported by Löser and Familia and colleagues, but were higher than those reported by Nishihara 14%, Darisetty 12.3%, and Shivakunun 11% 9,20,21,23,24. The abdominal decompression rates in this study are higher than those reported in other studies because of a longer duration for mucosal tunnel and myotomy in the current study, resulting in longer insufflation duration 25. When blood gas samples were examined in this stage, acidosis was identified in ABG indicating that submucosal and mediastinal absorption of CO 2 was greater than excretion with ventilation.…”
Section: Discussionsupporting
confidence: 80%
“…9,20,21,23,24 The abdominal decompression rates in this study are higher than those reported in other studies because of a longer duration for mucosal tunnel and myotomy in the current study, resulting in longer insufflation duration. 25 When blood gas samples were examined in this stage, acidosis was identified in ABG indicating that submucosal and mediastinal absorption of CO 2 was greater than excretion with ventilation. In addition, in this study, there was a significant increase in airway pressure because of pnomoperitonium, and PIP values were decreased by the use of veress needle for abdominal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was discharged on postoperative day 9. Okada et al[ 8 ] described this case previously in detail.…”
Section: Resultsmentioning
confidence: 96%
“…De-aeration might become necessary and can be accomplished with a percutaneous abdominal needle along with positive pressure ventilation with suitable ventilator settings. 14 All of the above complications may appear for the first time in the postprocedural period. At our hospital, patients presenting for POEM fast longer than usual and stay on clear fluids for 48 h. We used to perform this procedure in our inpatient facility; however, after gaining more experience, we now perform about half of such procedures in our outpatient facility and the patients are usually discharged the next day.…”
Section: Poemmentioning
confidence: 99%
“…Chest radiography might demonstrate variable pneumomediastinum and subcutaneous emphysema. De-aeration might become necessary and can be accomplished with a percutaneous abdominal needle along with positive pressure ventilation with suitable ventilator settings [ 14 ].…”
Section: Poemmentioning
confidence: 99%